Driver Drowsiness Detection System Using Sensors - Kusuma Kumari B.M; Sampada Sethi; Ramakanth Kumar P; Nishant Kumar; Atulit Shankar (International Journal of Informatics and Communication Technology (IJ-ICT), 2017)
A low-cost and simple distributed sensors model that is particularly suitable for measuring eye blink of the driver, accident and hand position on a steering wheel. These sensors can be used in automotive active safety systems that aim at detecting driver’s fatigue, a major issue to prevent road accidents. The key point of this approach is to design a prototype of sensor units, so that it can serve as platform for integrating different kinds of sensors into the steering wheel. Since the sensors are attached to the steering wheel, therefore they can’t be detached by the driver. It will also detect dangerous stylish driving which may lead to fatal accidents. The major drawback is that the eye blink sensors frame worn by the driver can be removed causing the sensor non-operational. The outcome is that the vibrator attached to eye blink sensor’s frame vibrates if the driver shuts his eyes for approximately 3 seconds and also the LCD displays the respective warning message. The wheel is slowed or stopped depending on the condition. This is accompanied by the vehicle’s owner being notified through the GSM module, so the owner can retrieve the driver’s location, photograph and a list of nearby police stations through an android mobile application. Therefore, driver can be alerted during drowsiness and the owner can be notified simultaneously.